Snack Product Processing and Business Management of Milkfish Crackers to Increase Local Potential - Endah Susilowati; Diah Hari Suryaningrum; Sari Andayani (Future Science, 2021)
The purpose of the Community Service Program for the Utilization of Science and Technology for the Community (PIKAT) is to provide training and assistance to the